Taninska lužila na osnovi bakrovih kompleksnih spojin - Tišler, Vesna (Les (Ljubljana), 1999)
In the teoretical part the composition of hydrolysed and condensed tannins is presented. First ones based on gallic acid, and the others based on catechin. Both components are bonding itself in complicated compositions, which are chemically tied on sugars, what complicates their structure even more. Main accent is on the throughly studying of tannin of three different wood species:picea, quebracho and chestnut, with basic monomers (stylben, catechin and gallic acid). Teoretical interpretation is used in practical part where making the stains or dyed cooper complex compositions from three sorts of tannin were studied.
Keywords: les; lužila; tanin; stilben; katehin; galna kislina